Jurnalisme Muter Searah : Konsep Jurnalistik yang Sejalan Dengan Ahlussunah Waljamaah - Widodo, Arif (IAINU Kebumen, 2022)
The murky cyber media has been recorded by the NU Cyber ​​Team and the Ta'lif wan Nasyr Institute (LTN) of the Nahdlatul Ulama Executive Board (PBNU). Recent searches have also found websites labeled Islam with posts of articles and news that are ethnic, religious, racial and inter-group (SARA) and radicalism that threatens the Unitary State of the Republic of Indonesia (NKRI). Meanwhile, PCNU Kebumen captured this by forming a Cyber ​​Media Team. The question arises, what is the concept of journalism that is in line with Ahlussunah Waljamaah (Aswaja). At least the concept that can be used as a guideline or reference for the PCNU Kebumen Cyber ​​Media Team while simultaneously dismissing posts that are SARA and radicalism through the packaging of news or articles (opinions) through the media managed by the team. As a result, news and opinion posts from the media managed by the PCNU Kebumen Cyber ​​Media Team are in line with Aswaja. To note, the existence of the media functions as an online communication media for information that is open to the public and or according to PCNU Kebumen policy can be opened to the public. So that the packaging of news and opinions also reflects the characteristics of NU, including tawasuth (middle / not extreme), tasamuh (tolerant) and tawazun (balanced).